Control of microgrids - Seah, Justin Nan Zheng (2019)
A microgrid is a localized group of electricity sources and loads that operates synchronously with the main grid. Together with distributed generation and energy storage system, it improved the reliability of microgrid through power condition system during islanding operations. Battery modelling have been research in many areas in the design and usage of battery in the energy storage system. This project aims to analyse the different battery models and simulate various load profiles through MATLAB Simulink. Battery models ranges from simple and complex models. However, simple models may not exhibit the most accurate results compared to complex models. Moreover, complex models may not be easier to implement in real life application compared to simple models. Thus, battery researchers are consistently looking for the model that can display the most accurate results and easy to build or implement. Load profile goes from continuous discharge current, pulse discharge current and the combination of both, to simulate real life applications and justify the practicality of the system. Percentage error is also used to determine the precision of the calculation between measured and theoretical values. As a result, the proposed battery model will display the battery runtime and I-V performance accurately and yet be simple enough to implement.